The end of a myth—Bt (Cry1Ab) maize does not harm green lacewings - Romeis, Jörg; Meissle, Michael; Naranjo, Steven E.; Li, Yunhe; Bigler, Franz (Frontiers in Plant Science, 2014)
A concern with Bt-transgenic insect-resistant plants is their potential to harm non-target organisms. Early studies reported that Cry1Ab-producing Bt maize and purified Cry1Ab harmed larvae of the green lacewing, Chrysoperla carnea. Although these effects could not be confirmed in subsequent studies, some authors still refer to them as evidence that Bt maize harms beneficial species. We provide a comprehensive review of the studies evaluating the effects of Bt (Cry1Ab) maize on C. carnea. The evidence indicates that this important predator is not affected by Bt maize or by the produced Cry1Ab protein. We discuss how conceptual models can assist environmental risk assessments, and we emphasize the importance of robust and reproducible studies.